CMOS Duobinary Transceiver for Multigigabit Communications - Aguirre, J.; Sánchez-Azqueta, C.; Guerrero, E.; Gimeno, C.; Celma, S. (Jornada de Jóvenes Investigadores del I3A, 2017)
This work presents a CMOS transceiver for amplitude duobinary modulation over an equalized 50-m step-index plastic optical fiber (SI-POF). Both duobinary precoder and decoder have been fabricated in 0.18-μm CMOS technology, enabling a bandlimited system of 700 MHz to operate at 3.125 Gbps with a consumption of 28.4 mW.